A general strategy to enhance the electrochemical activity and energy density of energy-storage materials through using sintering aids with redox activity: a case study of Mo4Nb26O77. Issue 37 (30th June 2022) - Li, Songjie; Gao, Jiazhe; Ou, Yinjun; Wang, Wenze; Zhang, Qian; Gao, Shangfu; Liu, Xuehua; Lin, Chunfu
Abstract : A general modification for the solid-state reaction preparation of energy-storage materials is explored through using sintering aids with redox activity. Abstract : The solid-state reaction method for energy-storage material preparations is simple and cost effective, thereby being suitable for industrialization. However, its sintering temperatures are generally high, resulting in large-sized (>1 μm) primary particles with low electrochemical activity. Here, based on a Mo4 Nb26 O77 model material, we explore a general modification of the solid-state reaction method through using sintering aids with redox activity and successfully prepare Mo4 Nb26 O77 with submicron-sized (∼200 nm) primary particles at a low sintering temperature of only 700 °C. The resultant high electrochemical activity of Mo4 Nb26 O77 and its additional Mo-based redox activity which originated from the MoO3 sintering aid enable its large practical capacity of 366 mA h g −1, which is the largest in the field of niobate anode materials. Mo4 Nb26 O77 further exhibits a relatively low working potential since more Nb 4+ ions are reduced to Nb 3+ ions at low potentials. Additionally, Mo4 Nb26 O77 has high rate performance and good cyclability when external Li + ions mainly occupy the interstices between the (010) crystallographic planes of its open and stable shear ReO3 crystal structure. Good low-temperature electrochemical properties are also achieved as a result of the high electrochemical activity. Therefore, this anode material has great practicability for high-performance Li + storage.